Uji Efikasi Formulasi Rizobakteri Pantoea agglomerans GTA24 dalam Mengendalikan Penyakit Rebah Semai yang Disebabkan oleh Sclerotium rolfsii pada Tanaman Kedelai - PARWATI, GUSTI AYU KOMANG CANDRA; KHALIMI, KHAMDAN; ADIARTAYASA, WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.3, No.4, Oktober 2014, 2014)
ABSTRACT Efficacy Test of Pantoea agglomerans GTA24 rhizobacteria Formulations in Controling Damping off  Disease Caused By Sclerotium rolfsii on Soybean Plants The experiment aimed to determine the effectiveness of the P. agglomerans GTA24 rhizobacteria formulations in controlling damping off diseases. The experiment was conducted in vitro and in greenhouse test. The experiment was a randomized complete blocks with five replications. The treatment consists of four types of P. agglomerans GTA24 rhizobacteria formulations is pellets formula, powder formula, compost formula, and the gel formula. The results showed that the application of P. agglomerans GTA24 formulations significantly inhibited the fungal growth. P. agglomerans GTA24 showed strong inhibitory activity agains    Sclerotium rolfsii on PDYA medium percentage of inhibitory activity about 96,30%. The lowest disease incidence was attained by the treatment of gel formula, in which only 15,56% of the soybean plants were infected.   Keywords : rhizobacteria formulations, damping off disease, soybean plants
Keywords: rhizobacteria formulations, damping off disease, soybean plants